Balanced Bilingualism: Patterns of Contact Influence in L1 and L2 Turkic and Bakhtiari Speech in Juneqan, Iran. Issue 3 (3rd July 2020) - Anonby, Erik; Schreiber, Laurentia; Taheri-Ardali, Mortaza
Abstract : Most studies on language contact in Iran have focused on the effects of Persian on the country's minority languages. There are also many cases where large regional languages such as Azeri, Kurdish, Balochi, Lori and Bakhtiari exert an influence on smaller regional languages, and a few studies have appeared on this topic. This paper examines the effects of language contact in the city of Juneqan in Chahar Mahal va Bakhtiari Province, Iran, where the position of two minority languages—Bakhtiari and Qashqai Turkic—appears to be evenly balanced. The analysis is based on a comparison of L1 and L2 speech from two bilingual individuals with a different L1, as found in responses to the Atlas of the Languages of Iran (ALI) questionnaire. Drawing on examples from lexicon, phonology and morphosyntax, the article argues that the equivalent influence of each language on the first- and second-language speech of members of the other language community is likely achieved not by simple equal status, but through the counterbalancing of regional Bakhtiari dominance with majority mother-tongue Turkic population in this city.